PROGRESS IN HEALTH COVERAGE AMONG INDONESIAN OLDER PEOPLE TOWARD THE WORLD HEALTH ORGANIZATION’S DECADE OF HEALTHY AGING 2021-2030 - Puspitasari, Mardiana Dwi; Rahardja, Mugia Bayu; Surbakti, Indra Murty (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Introduction. Older people are associated with health decline and age-related disability. Person-centered integrated care is an action plan for the 'Decade of Healthy Aging 2021-2030' to ensure older people enjoy healthier lives. Purpose. To participate in the Decade movement, evidence of the progress in health coverage among Indonesians elderly from 2015 to 2022 should be presented. Methods. This study uses the 2015, 2020, and 2022 National Socio-Economic Survey (SUSENAS) datasets with a sample of 94,326, 121,961, and 122,344 elderly aged 60 and over, respectively. Univariate analysis is used to determine the percentage of elderly utilizing outpatient treatment between 2015 and 2022. Results. The proportion of elderly without health insurance fell from approximately 45.4 percent in 2015 to 26.4 percent in 2015, and 26 percent in 2022. However, the proportion of older people with health insurance and a health problem but not seeking outpatient treatment rose from around 35.8 percent in 2015 to 45.2 percent in 2020, and 48.2 percent in 2022. Self-medication has been the highest prevalent reason for not utilizing outpatient treatment over time. Self-medication increased from about 57.5 percent in 2015 to 62.1 percent in 2020 and 73.9 percent in 2022. Only about 2.8 percent of the elderly did not utilize outpatient treatment in 2022 due to the COVID-19 pandemic. Conclusion. As self-medication was the most common reason, community awareness and collaboration with health care providers should be encouraged to carry out person-centered integrated treatment.